(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
This paper is focused on the description of an assemblage of ceratitids collected more than 50 years ago by C. Renz from the Han-Bulog Limestone of Hydra (Greece), up to the present never described. The identified forms are Asseretoceras camunum (Assereto, 1963), Megaceratites aff. fallax Balini, 1992b, Ronconites sp. n. A, "Kellnerites" sp. ind., Nevadites sp. ind. Two ceratitids of uncertain attribution are also described. These species have only paleoecological implications, since a stratigraphic bed-by-bed sampling has not been performed. A. camunum and the genera Megaceratites and Ronconites are reported for the first time from the Han-Bulog Limestone. Megaceratites and Ronconites are also reported for the first time out of the Southern Alps.